Work, Play, and Performance in the Southern Tobacco Warehouse - Gaddis, Elijah (Material Culture Review / Revue de la culture matérielle)

(untitled) (Cape Breton University Press, 2019)
This paper examines tobacco warehouses in the southern United States as sites of both work and play. Using a performative approach in the study of architecture that is rooted in folklife methodology, the essay claims these quotidian working structures as places of celebratory potential amid the strictures of Jim Crow spatial segregation. In particular, it focuses on a series of massive dances held in the elaborately decorated warehouses during the early-to-mid-20th century. During these dances, Black celebrants turned the restrictive social and economic working spaces of the tobacco warehouse into places of radical potential and pleasure. The claims of this essay are supported by both conventional architectural documentation and the oral testimonies of a variety of tobacco workers, musicians, and dancers, who made use of the warehouses for a variety of often conflicting purposes. Told together, their narratives emphasize both spatialized resistance to segregation, and the importance of the ephemeral archives of individual stories and memories to the study of vernacular architectural history.